Akurasi Arah Kiblat Masjid di Ruang Publik - Anisah Budiwati (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
This research explores the concept of understanding of mosque managers in the public space about the importance of facing the direction of Qibla. Samples Mosque located in the public space of the Hospital Jogja International Hospital, Adisutjipto Airport and Mall Plaza Ambarrukmo be proof of the tendency of pattern of understanding of managers of religious orders to face the direction of Qiblah correctly. By using qualitative analysis method and data collection method in the form of observation, interview and documentation, it is found that first, that understanding of mosque managers in public space at three places reflects the quality of life of Islami ie measuring to the expert so that the direction of qibla . Secondly, the accuracy of the direction of the mosque building in the public space in Sleman Yogyakarta is included in the category of accurate with the maximum reason for the 6 minute arc disturbance, where the direction of the largest deviation on the mosques is 0o 1 '20.8 "or equivalent to 3,074 km which means still leads the city of Mecca.Keywords: Accuracy, Understanding and Mosque in Public Space Penelitian ini menggali konsep pemahaman para pengelola Masjid di ruang publik tentang pentingnya menghadap arah kiblat. Sampel Masjid yang berada di ruang publik yakni Rumah Sakit Jogja International Hospital, Bandara Adisutjipto dan Mall Plaza Ambarrukmo menjadi bukti kecenderungan pola pemahaman pengelola terhadap perintah agama untuk menghadap ke arah kiblat dengan tepat. Dengan menggunakan metode analisis kualitatif dan metode pengumpulan data berupa observasi, wawancara dan dokumentasi diperoleh hasil penelitian, pertama bahwa pemahaman para pengelola masjid di ruang publik pada tiga tempat tersebut mencerminkan kualitas hidup Islami yakni melakukan pengukuran kepada pihak ahli sehingga arah kiblat sesuai dengan keilmuan astronomi. Kedua, akurasi atau ketelitian arah kiblat bangunan Masjid di ruang publik di Sleman Yogyakarta termasuk dalam kategori akurat dengan alasan maksimal penyimpangan 6 menit busur, di mana arah penyimpangan paling besar pada masjid-masjid tersebut adalah 0o 1’ 20,8” atau setara 3,074 km yang berarti masih mengarah kota Mekah.Kata kunci: Akurasi, Pemahaman dan Masjid di Ruang Publik